Fishing Vessel Position Monitoring System Based on the Internet of Things (IoT) - Yusuf, Andi Jaya Wardanah; Mahmuddin, Faisal; Shintarahayu, Balqis; Budiman, Budiman (Naval Architecture Department, Kalimantan Institut of Technology, 2025)
The life of traditional fishermen in Indonesia is closely related to the sea. Coastal communities rely on marine products as a source of daily livelihood. However, in recent years, many traditional fishermen have disappeared at sea. Based on those problems, it is necessary to create a tool in an effort to develop security for fishermen in the form of a position monitoring system that is able to reduce the risk of fishermen disappearing in the middle of the sea by using a better and more practical system. This research developed a system for monitoring the position of fishing vessels using an Arduino microcontroller. Based on the results of testing and analysis in this research, it is known that the position monitoring system on fishing vessels uses a NodeMcu LoLin V3 type microcontroller as a data processor and GPS Ublox Neo-6M as a sensor which functions to send location points on a fishing vessel. The coordinates of the location of the fishing vessel are then displayed on the smartphone via the Blynk application. So when the tracking tool is connected to the internet, the average difference in distance precision between the Ublox Neo 6M GPS and Google Maps is 2.3 meters. For input speed from NodeMcu LoLin v3 and GPS Ublox Neo 6M to the Blynk application displayed on the smartphone. Monitoring for 40 seconds showed that the data speed displayed was one location data per second. From the results of the tests carried out, this tool can work well and can be used to monitor fishing vessels continuously.